36 A Randomised Trial to Compare How Undergraduates Diagnose Common Ear Pathology Using A Smartphone Otoscope and Standard Otoscope in A Simulated Setting. (4th May 2021) - Schuster-Bruce, J; Ali, A; Van, M; Rogel-Salazar, J; Ofo, E; Shamil, E
Abstract: Introduction: Competent otoscopy is a key otolaryngology skill for a broad range of medical careers, yet undergraduate's confidence to perform otoscopy is reported as low. This study aimed to evaluate whether a smartphone-otoscope could enhance medical undergraduates recognition of common ear pathology. Method: 52 medical students were randomised into a standard group (traditional otoscope) and an intervention group (smartphone-otoscope). Following a short didactic presentation, participants were asked to diagnose four simulated pathologies. Force response items and 5-point Likert scales loaded on an electronic platform recorded their diagnosis and their perceptions towards the otoscope. Results: The smartphone-group (n = 20) had higher overall rates of correct diagnosis compared to control (n = 22) (84% vs 39%, p = <0.001). Only the grommet station did not show a significant improvement between the two groups (100% vs 91%, p = 0.49). 90% (n = 20) of participants felt the smartphone-otoscope was preferential for their learning. The same number expressed they want to use it in future learning. The remainder were indifferent. Conclusions: The smart-phone otoscope enabled learners to better observe and recognise middle ear pathology. This popular learning tool has the potential to accelerate the learning curve of otoscopy and therefore improve the proficiency of future doctors at recognising middle ear diseases.